Influence of Ginger (Zingiber officinale) on Sperms Parameters, Spermatogenesis and Sexual Hormones of Male Mice - Alessia, Mohammed S; Shalaby, Amr A; Alkarim, Hind Abd; Ibrahim, Nasir A; A.B.M, Sharif Hossain; Stam, Ghanim (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The use of ginger (Zingiber officinale), and specifically its medicinally active rhizome, has gained popularity among modern physicians in recent years. The effect of an aqueous extract of ginger was investigated on morphological of seminiferous tubules of mice and sperm parameters of semen for 90 male mice that were divided into three groups of 30 mice for each group. The experimental groups split into two groups each included 30 mice. (G.1) received 50mg/k/body weight and (G.2) received 100 mg/k/ body weight of ginger were dissolved in drinking water for 21 respectively days. This study aimed to evaluate the effect of ginger on Semen characteristics, sex hormones and the histology of the testes to show the spermatogenesis affected by ginger. In the present study we showed that, the average of body weight decreased in all experimental ginger-treated groups (G1) and (G2) The testes weight decreased in both experimental groups, compared with the control group (mice without treated only distilled water); however, this decrease was statistically significant in body weight (p<0.05).There was no significant testes weight decreased in experimental groups (G1) compared with the control group. The sperm counts increased in all experimental groups relative to the control group, although this increase was not statistically significant in group (G1), and there was statistically significant in experimental group (G2). However, there were highly significant increases (p<0.05) in sperm motility and viability in all treated groups (G1 and G2) compared with the control group. The effects of ginger, on Sex hormones and antioxidant, was significantly different (p> 0.05) in Follicle-stimulating hormone (FSH), Luteinizing hormone (LH) and testosterone hormone ,total antioxidant capacity (TAC), and malondialdehyde (MDA) in all animal experiment when compared with control. Furthermore the histological study of testes showed a significant increase in the lumina spermatozoa at the level of Spermatogonia and primary spermatocytes.